Facilitating entrepreneurship in higher education through practitioner integration: a closer look at the “entrepreneur in residence” initiative - Aluthgama-Baduge, Chinthaka; Rajasinghe, Duminda; Ilonen, Sanna; Gilman, Mark (Emerald, 2025)
Purpose
We investigate practitioner integration (PI) within higher education institutions (HEIs) by taking a closer look at the entrepreneur in residence (EiR) initiative. Engaging experienced entrepreneurs through EiR initiatives to facilitate entrepreneurship education (EE) has become a familiar PI model within HEIs; nevertheless, how EiRs perceive their role and integration in academia has been under-researched. We deepen the understanding of how EiRs facilitate EE and their role and fit into academia.
Design/methodology/approach
This qualitative research employs interpretative phenomenological analysis (IPA) as the methodology. Following IPA guidance, we purposively selected seven EiRs working within HEIs and conducted one semi-structured interview with each participant. The data were analysed using IPA data analysis guidelines.
Findings
The findings suggest that the previous experiences of EiRs influence their confidence, skills and intrinsic motivation in their role in academia. EiRs play a multifaceted role that goes beyond students and simple educational activities to develop trust and understanding among university communities while bridging academic–practitioner, structural and communication gaps that hinder entrepreneurship in higher education. The study reveals the disconnected nature of EiRs’ role in academia and the tensions between academics and EiRs.
Originality/value
This study provides space for unheard EiRs’ voices, enriching the scarce EiR literature by advancing our knowledge about their role and fit in academia. The novel insights into the role of EiRs broaden the scope of EE to university communities beyond students. The findings deepen our understanding of how EiRs foster entrepreneurship by acting as a trust ladder and developing a networked approach to supporting university stakeholders. The challenges lie in how EiRs are integrated and the tensions between academics and practitioners. We also found that EiRs with greater authority, prior exposure to strategic roles within the institution and strong relationships with institutional leaders perform their role efficiently. Hence, this study establishes the importance of a more coordinated, strategic approach to PI within HEIs.